Turbulent Mixing in the Upper Arctic Ocean Energized by Interactions of Tidally‐Forced Waves With Mesoscale Shear - S. F. Reifenberg; I. Fer (Geophysical Research Letters)
Abstract High‐resolution observations in Fram Strait reveal complex interactions across scales, highlighting the role of internal waves in enhancing mixing within the meltwater halocline. A day‐long microstructure survey from drifting ice that traversed an anticyclone in summer shows rotating shear and straining in the halocline, resulting in low Richardson number layers coincident with turbulent patches and gradients in oxygen and chlorophyll. Year‐long data from an adjacent mooring demonstrate that increased shear variance can be related to upward‐propagating wave energy, generated by tidal forcing at the seafloor and amplified by mesoscale shear near the surface. These waves contain compound tides and overtones with spectral peaks at 3 and 4 cycles per day. Mesoscale variability modulates internal wave shear, influencing turbulent mixing and ecosystem dynamics. Our findings underscore the importance of cross‐scale interactions in driving turbulent mixing, with implications for water mass transformations, sea ice melt, and primary production in a changing Arctic.